Religion, tradition, and restorative justice in Sierra Leone - Graybill, Lyn S. (Notre Dame : University of Notre Dame Press, 2017)
In this groundbreaking study of post-conflict Sierra Leone, Lyn Graybill examines the ways in which both religion and local tradition supported restorative justice initiatives such as the national Truth and Reconciliation Commission (TRC) and village-level Fambul Tok ceremonies.
Postwar transitional justice -- Role of the inter-religious council -- The Sierra Leone Truth and Reconciliation Commission -- Women and transitional justice -- Popular views of the TRC and the special court -- Perceptions of religious leaders -- Traditional reconciliation practices -- Unfinished business -- The instrument -- Interviews of religious leaders.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Master record variable field(s) change: 072
Keywords: Sierra Leone. -- Truth and Reconciliation Commission; Sierra Leone. -- Truth and Reconciliation Commission; Sierra Leone -- Religion -- History -- 20th century; Religion and politics -- Sierra Leone; Transitional justice -- Sierra Leone; Reparations for historical injustices -- Sierra Leone; Restorative justice -- Sierra Leone; Reconciliation -- Political aspects -- Sierra Leone; BODY, MIND & SPIRIT -- Gaia & Earth Energies; RELIGION -- Christianity -- General; Reconciliation -- Political aspects; Religion; Religion and politics; Reparations for historical injustices; Restorative justice; Transitional justice; Sierra Leone; RELIGION / Ethics; 1900-1999; History; Electronic books